In vitro culture of Piper longum Linn. - Rajkarnikar, K. M.; Bhatta, G. D. (Journal of Plant Resources, 2008)
In vitro clonal propagation of Piper longum is attempted for rapid multiplication using shoot tip explants. The explants regenerated micro shoots along with few callus and embryoids on the Murashige and Skoog (1962) supplemented with 1mg/l BAP and 0.1mg/l NAA. The NAA concentration of the same medium was lowered to 0.01 mg/l and added 10% coconut milk for subculture. For rooting, these regenerated microshoots were transferred to non-sterile sand, after acclimatization. They initiated roots within 15 to 20 days and transferred to polybags for further growth and for field transfer. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 76-79